Balanced Nutrition in School-Age Children - Fahmi Fuadah; Gurdani Yogusutanti; Tri Ardayani; Neti Sitorus; Linda Hotmaida (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service aims to implement community nutrition intervention activities in overcoming nutritional problems in Pamengkang Village, Kramatwatu District, Serang Regency, Banten Province. This community service activity was carried out by onsite / direct visit to Pamengkang Kramatwatu District, Serang Regency, Banten Province through a process of planning, implementation and evaluation on February 1, 2023. Followed by 30 health cadres, 30 mothers who have babies, and 30 elementary school children consisting of grades 3, 4, 5. Data collection techniques using documentation. The outputs of this activity are in the form of a certificate of Community Service, a report on the Activity "Interprofessional Collaboration for Public Health Handling Stunting in Pamengkang Village, Kramatwatu District, Serang Regency, Banten Province", and Collaborative Publications in the Field of Material (Community Service Articles). The community service activities carried out went well. It can be seen from the enthusiasm of cadres, mothers and children during the activity.